Preparation and characterization of zein/pectin-based phytosterol nanodispersions and kinetic study of phytosterol release during simulated digestion in vitro. (June 2020) - Feng, Simin; Wang, Dan; Gan, Ling; Shao, Ping; Jiang, Ligang; Sun, Peilong
Abstract: The purpose of this study was to fabricate zein/pectin-based stigmasterol nanodispersions and improve their stability. The optimal condition of pectin/zein ratio of stigmasterol nanodispersions was 1:10. In this condition, the average particle diameter, Zeta-potential, encapsulation efficiency and loading amount of nanodispersions were 584.40 ± 69.55 nm, −38.32 ± 0.23 mV, 84.96 ± 3.28% and 15.45 ± 0.59 g/100g, respectively. The scanning electron microscope (SEM) and differential scanning calorimetry (DSC) results showed that stigmasterol and zein were successfully encapsulated by pectin which formed elastic network gel on the outside of the particles. With presence of pectin, the stability of the nanodispersions in different environmental and simulated digestion condition had been improved. Highlights: Zein/pectin-based stigmasterol nanodispersions were fabricated. With presence of pectin, the stability of the nanodispersions had been improved. The nanodispersions were stable in the stomach. Pectin formed elastic network gel on the outside of the particles.